Switchable and Dual-Tunable Multilayered Terahertz Absorber Based on Patterned Graphene and Vanadium Dioxide - Hongyao Liu; Panpan Wang; Jiali Wu; Xin Yan; Xueguang Yuan; Yangan Zhang; Xia Zhang (Micromachines, 2021)
In this paper, a switchable and dual-tunable terahertz absorber based on patterned graphene and vanadium dioxide is proposed and analyzed. By controlling the Fermi level of graphene and the temperature of vanadium dioxide, the device’s function can be switched and its absorbing properties can be tuned. When the vanadium dioxide is in an insulator state, the device can be switched from near-total reflection (>97%) to ultra-broadband absorption (4.5–10.61 THz) as the Fermi level of graphene changes from 0 to 0.8 eV. When the vanadium dioxide is changed to a metal state, the device can act as a single-band absorber (when the Fermi level of graphene is 0 eV) and a dual-band absorber with peaks of 4.16 THz and 7.3 THz (when the Fermi level of graphene is 0.8 eV). Additionally, the absorber is polarization-insensitive and can maintain a stable high-absorption performance within a 55° incidence angle. The multilayered structure shows great potential for switchable and tunable high-performance terahertz devices.